Evaluation of Probiotic Characteristics of Lactic Acid Bacteria Isolated from Two Commercial Preparations Available in Indian Market - Singhal, Neelja (Indian J Microbiol, 2018)
The enormous health benefits associated with probiotics has resulted in an increased consumption of probiotic supplements. Several factors like regular sub-culturing, storage, unfavourable conditions etc. might compromise the efficacy and/or safety of lactic acid bacteria which are the major components of many probiotic preparations available in the market. The present study evaluated the probiotic characteristics and safety of probiotic bacteria isolated from two preparations available commercially in India. The products did not specify the genera, species or strains of the bacteria used. These were cultured using standard microbiological methods for cultivation of lactic acid bacteria. Bacteria were identified by PCR amplification and sequence analysis of 16S rRNA gene. Microbiological and molecular analyses revealed that both preparations contained homogenous population of Enterococcus faecium and Pediococcus acidilactici respectively. Assessment for several essential and desirable probiotic properties revealed that both the probiotic strains were safe and resistant to salt, lysozyme, bile salt and common antibiotics. The probiotic preparation containing P. acidilactici was better than that containing E. faecium as it survived in low pH and showed bile salt hydrolase activity. The probiotic preparation containing P. acidilactici also exhibited cholesterol-lowering activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12088-018-0762-9) contains supplementary material, which is available to authorized users.